2010
DOI: 10.7124/bc.000160
|View full text |Cite
|
Sign up to set email alerts
|

A mobile genetic element in Serratia marcescens, a causative agent of onion disease

Abstract: Aim. To screen mobile genetic elements (MGE) in the bacterium which caused decay of field-grown onion bulb and to study an integron and gene cassettes associated. Methods. Polymerase chain reaction (PCR) and PCR products sequencing were used for both the bacterium and MGE identification. Terminally-labeled Restriction Fragment Length Polymorphism (TRFLP) analysis was performed for detection of any bacterium in the onion bulb tissue. Results. The bacterium, which caused field-grown onion decay, was identified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The diversity of roles that can be assumed by the same bacterial species, as Serratia marcescens , goes from plant grow promoting to phytopathogen through the acquisition of genetic mobile elements or environmental stimuli [42,43]. Understanding all the involved factors is important in order to develop strategies to control B. xylophilus dispersions.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of roles that can be assumed by the same bacterial species, as Serratia marcescens , goes from plant grow promoting to phytopathogen through the acquisition of genetic mobile elements or environmental stimuli [42,43]. Understanding all the involved factors is important in order to develop strategies to control B. xylophilus dispersions.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, the initial comparison between genomes (draft or completed) will elucidate genetic differences between genomes reflecting the diversity of assumed roles by strains of the same bacterial species from different environments. In case of Serratia marcescens , a second example, this reaches from being a plant growth promoter (Dong, Gu, Guo, Xun, & Liu, ), specially under plant stress, to acting as a phytopathogen through the acquisition of genetic mobile elements with an integron harboring genes that take part in the histidine metabolism (Ovcharenko et al., ) or responding to environmental stimuli (Zhang et al., ).…”
Section: Bacterial Genomics Relates To Pwnmentioning
confidence: 99%
“…Mobile genetic elements probably contributed to the acquisition of the aforementioned genes, a hypothesis supported by the over‐representation of a transposase in CCS (Zhang et al ., ). In addition, an onion‐infecting S. marcescens strain contains a potentially pathogenesis‐promoting mobile genetic element (Ovcharenko et al ., ). These findings suggest that the versatility of S. marcescens strains is a result of mobile genetic elements, and that CCS could have specialized in this fashion.…”
Section: Walled Phloem‐limited Bacteriamentioning
confidence: 97%
“…It is unclear where in the vector CCS is maintained, and research has shown CCS can overwinter in dormant A. tristis (Pair et al, 2004;Purcell and Finlay, 1979;Wayadande et al, 2005). Other S. marcescens strains are also plant pathogens, but are not insect vectored or phloem limited (Gillis et al, 2014;Ovcharenko et al, 2010;Wang et al, 2014). These strains, and the generalist nature of A. tristis, raise the intriguing possibility that CCS is an example in which a pathogen first infected plants before evolving to associate with an insect vector and becoming phloem limited (plant-first evolution) (Nadarasah and Stavrinides, 2011).…”
Section: Serratia Marcescens: From Generalist To Specialistmentioning
confidence: 99%